Chemotherapy and electrotherapy significantly fast tracks virus elimination in sweetpotato - Gatimu, R.; Ogero, K. (2025)
This research brief reports on experiments conducted at the Roots, Tubers and Bananas – East Africa Germplasm Exchange Laboratory (RTB-EAGEL) in Nairobi, Kenya, evaluating the efficiency of chemotherapy and electrotherapy in eliminating viruses from infected sweetpotato plants. Using human antivirals ribavirin and acyclovir, and electrotherapy at 15mA for 30 minutes, researchers successfully eliminated Sweetpotato chlorotic stunt virus (SPCSV) and Sweetpotato feathery mottle virus (SPFMV) within 5 and 3 months respectively—compared to the traditional 13 months using thermotherapy and meristem culture. Sweetpotato leaf curl virus (SPLCV) could not be fully eliminated, suggesting further optimization. The study demonstrates the potential for these treatments to accelerate production of virus-free early generation seed for sweetpotato.